Efeito dos sistemas de preparo sobre os atributos físicos do solo e balanço de carbono baseado no desenvolvimento do trigo irrigado - Silva, Wininton Mendes da (2012)
The objective of this work was to study the effect of tillage systems on soil physical properties and carbon balance based on the development of irrigated wheat crop in a Red-Dark typical soil of Tangará da Serra – MT. The treatments are three soils tillage, namely: conventional tillage, minimum tillage and non-tillage. The soil physical properties evaluated at 42 and 97 days were: soil density, total porosity, macro and microporosity. The carbon balance within each tillage was calculated by the ratio of total carbon input into the system via crop biomass (shoot and root) minus the total loss of carbon as C-CO2 from the corresponding period in the crop cycle. Of the vegetation indices of culture was assessed shoot dry matter, in four times throughout the crop cycle, and the increase of root dry matter, which was estimated by the ratio between the growth of shoots and roots based on degree day of culture development. The soil physical properties in different tillage had significant influence on the dry matter accumulation of shoots and roots of culture. In the carbon balance the non-tillage had the highest carbon accumulation (p <0.05) among tillage systems and PC and PM did not differ. The total accumulated loss of C-CO2 in the wheat cropping systems are higher at night than during the day regardless of tillage adopted. The efflux of carbon nightly suffers significant variation with the increase of shoot dry matter of culture throughout its development.